Investigating the effects of construction industry noise on workers’ cognitive performance and learning efficiency - Cao, Xinying; Lu, Yian; Zheng, Decheng; Qin, Peicheng (Frontiers in Human Neuroscience, 2025)
Despite growing industrialization, the cognitive and psychological impacts of construction noise on workers remain inadequately addressed in empirical research. This study examines the impact of different noise types and intensities on the cognitive performance and learning efficiency of construction workers, using electroencephalogram (EEG) and behavioral data. Specifically, it analyzes the effects of complex noise and steady noise on workers’ attention, mental workload, mental fatigue, and mental stress. The results indicate that complex noise significantly reduces learning efficiency, notably impairing accuracy and reaction time relative to steady noise. This adverse effect is attributed to the unpredictability and variability of complex noise, which disrupts workers’ cognitive processing and heightens mental fatigue. In contrast, although steady noise does not significantly impact mental workload, it induces greater mental fatigue and mental stress than complex noise, especially at high noise levels. The findings also reveal that workers develop some level of adaptation to continuous noise, mitigating its overall impact on learning efficiency. However, elevated noise levels, regardless of type, consistently lead to significant declines in attention and increases in mental stress and mental fatigue. This research makes an original contribution by providing evidence-based insights into the interaction between noise characteristics and worker cognition, offering practical implications for targeted noise management strategies to improve learning efficiency and well-being in construction environments.